Management of Bilateral Complicated Cataract in Convalescent Stage of Vogt- Koyanagi-Harada Syndrome - Faradina R. Quamila; Ovi Sofia; T. Budi Sulistya (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2021)
Introduction: The incidence of complicated cataract in VKH syndrome in Japan is 35% and 40% in US. Cataract extraction surgery is advisable for evaluating posterior segment and improving visual acuity. This study is reporting management of bilateral complicated cataract in Vogt-Koyanagi- Harada syndrome convalescent stage under corticosteroid coverage. Purpose: To report the diagnostic approach and successful management of bilateral complicated cataract in convalescent stage of Vogt-Koyanagi-Harada syndrome Case Presentation: A 24-year old woman came to the outpatient clinic of Dr. Saiful Anwar Hospital Malang complaining of blurred vision on both eyes which worsen 2 months prior to visit. It was accompanied with headache, nausea, fever, hair loss, and facial hair whitening started 1 month afterwards. General examination showed alopecia and poliosis. The visual acuity of both eyes were hand motion. Anterior segment examination showed polymorphic old KPs, 4+ flare and 4+ cells, secluded pupil, and cataract in both eyes. Vitritis and choroidal thickening were noted from ultrasound examination. Laboratory examination results were within normal limit. She was diagnosed with Vogt- Koyanagi-Harada syndrome convalescent stage with complicated cataract and had been treated with combination of oral corticosteroid and azathioprine. Synechiolysis and cataract extraction of left eye were performed under oral corticosteroid and posterior subtenon triamcinolone injection coverage. There was improvement of visual acuity and controlled inflammation postoperatively. Conclusion: Significant visual improvement of left eye was shown after cataract extraction surgery under adequate inflammation control preoperatively. There was no relaps of uveitis during 6 months follow up.